Aggregate fractal dimensions and thermal conduction in nanofluids - Gharagozloo, Patricia E.; Goodson, Kenneth E. (Journal of applied physics, 2010)
The mechanism producing enhanced thermal conductivities of nanofluids has been the subject of much debate. The formation of aggregates allowing for percolation paths within the fluid has shown the most promise. This work studies the aggregate formation of a nanofluid and compares the results to earlier thermal conductivity measurements and Monte Carlo simulation results. Static light scattering is employed to measure the fractal dimension of aggregates formed in the nanofluid over time at various temperatures and concentrations. As expected, aggregates form more quickly at higher concentrations and temperatures, which explains the increased enhancement with temperature reported by other research groups. The permanent aggregates in the nanofluid are found to have a fractal dimension of 2.4 and the aggregate formations that grow over time are found to have a fractal dimension of 1.8, which is consistent with diffusion limited aggregation. Predictions indicate that as aggregates grow the viscosity increases at a faster rate than thermal conductivity making the highly aggregated nanofluids unfavorable, especially at the low fractal dimension of 1.8.